Associations between body fat percentage, waist-to-hip ratio, physical activity, and elevated blood pressure among junior high school adolescents in Jakarta - Mediana Puji Larasati; Iin Fatmawati; Muh. Nur Hasan Syah (AcTion: Aceh Nutrition Journal, 2026)
Elevated blood pressure affects approximately three out of ten Indonesian adolescents aged ≥15 years, increasing their risk of adult hypertension. Adiposity indicators, including Waist-to-Hip Ratio (WHR) and body fat percentage (BF%), are biologically linked to insulin resistance, while high fat intake may increase vascular resistance. However, evidence regarding adolescents in metropolitan settings, such as Jakarta, remains limited. This study examined the associations between fat intake, WHR, BF%, physical activity, and elevated blood pressure among adolescents. A cross-sectional study was conducted among 219 ninth-grade students at State Junior High School 182 Jakarta, selected using stratified random sampling. Blood pressure was categorized as normal (<120/80 mmHg) or elevated (≥120/80 mmHg). Data were collected through interviews and completion of the SQ-FFQ, PAQ-C/PAQ-A), anthropometric measurements, and Bioelectrical Impedance Analysis. Ethical approval was obtained (No. 037/KEPK/UNPRI/V/2025). Chi-Square analysis revealed that abdominal obesity (WHR) and high BF% were significantly associated with elevated blood pressure (p=0,017 and p<0,001), whereas fat intake (p=0,132) and physical activity (p=0,694) were not. Multivariate logistic regression identified BF% as the strongest determinant (p<0,001; OR=7,393; 95% CI=3,748-14,581) of elevated blood pressure. In conclusion, adiposity, particularly an elevated BF%, is a key driver of elevated blood pressure in urban adolescents, underscoring the need for early obesity-focused interventions.